Reflective Thinking Skills Among Learners of The Faculty of Education at Tishreen University (A field Study at Tishreen University) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The Purpose of The Current Research Was to Determine the Reflective Thinking Skills of The Learners of The Faculty of Education at Tishreen University. The Research Made Use of The Descriptive Approach. The Research Sample Was Stratified Random Comprised of (215) Learners from The Faculty of Education at Tishreen University. To Achieve the Objectives of The Research, Scale Tool Designed by The Researcher Was Used Which Consisted of (22) Items is Sub-Divided into (4) Domains Represent Reflective Thinking Skills. The Validity and Stability Tool Had Been Verified and Established, The Results Revealed That the Determine the Reflective Thinking Skills (Habitual Action, Understanding, Reflect, and Critical Reflect) Were Being Practiced by The Learners Regardless Any Discrimination Due to Scientific Specializations, Gender, and Studying Years with Minor Differences. The Difference Which Subsists Was That the Overall Reflective Thinking Skills Were Better Among Curricula and Education Methods Department Learners, Females, and The Fifth year Learners. and to Achieve Deep Understanding for The Fennomen There Were Some Suggestions Such As. Qualitative Studying to The Relationship Between the Reflective Thinking Skills of The Learners and The Situations Which Are Needed the Practical Applications.
Keywords: Reflective Thinking Skills, Habitual Action, Understanding, Reflect, and Critical Reflect.